BMI and atrial fibrillation recurrence post catheter ablation: A dose‐response meta‐analysis. (5th March 2021) - Pranata, Raymond; Henrina, Joshua; Yonas, Emir; Putra, Iwan C. S.; Cahyadi, Irvan; Lim, Michael A.; Munawar, Dian A.; Munawar, Muhammad
Abstract: Introduction: The evidence on the association between obesity and atrial fibrillation (AF) recurrence was equivocal. We aimed to evaluate the dose‐response relationship between body mass index (BMI) and AF recurrence and adverse events. Methods: A systematic literature search was conducted using PubMed, Europe PMC, EBSCO, ProQuest and Cochrane Library. Obesity was defined as BMI ≥28 kg/m 2 . The primary outcome was AF recurrence, and the secondary outcome was adverse events. Adverse events were defined as procedure‐related complications and cardio‐cerebrovascular events. Results: There were a total of 52, 771 patients from 20 studies. Obesity was associated with higher AF recurrence (Odds ratio [OR] 1.30 [95% confidence interval [CI] 1.16‐1.47], P < .001; I 2 : 72.7%) and similar rate of adverse events (OR 1.21 [95% CI 0.87‐1.67], P = .264; I 2 : 23.9%). Meta‐regression showed that the association varies by age (coefficient: −0.03, P = .024). Meta‐analysis of highest versus lowest BMI showed that the highest group had higher AF recurrence (OR 1.37 [95% CI 1.18‐1.58], P < .001; I 2 : 64.9%) and adverse events (OR 2.02 [95% CI 1.08‐3.76], P = .028; I 2 : 49.5%). The linear association analysis for AF recurrence was not significant ( P = .544). The dose‐response relationship for BMI and AF recurrence was nonlinear (pnonlinearity < 0.001), the curve became steeper at 30‐35 kg/m 2 . For adverse events, an increase of 1% for every 1 kg/m 2 increase in BMI (OR 1.01 [95% CI 1.00‐1.02], P = .001), the relationship was nonlinear (pnonlinearity = 0.001). Conclusion: Obesity was associated with higher AF recurrence in patients undergoing catheter ablation. High BMI might be associated with a higher risk for adverse events. PROSPERO ID: CRD42020198787.